Meta Analisis Pengaruh Model Contextual Teaching and Learning terhadap Berpikir Kritis Siswa pada Mata Pelajaran Fisika - F. Simamora, Gabriella; Triany M, Kristina; Fatwa, Islami (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2022)
At the present time there are still many teachers who apply the lecture method in learning, especially physics so that it does not activate students in the learning process. While at this time students to be able to think critically in the learning process. One of the learning models that can improve students' critical thinking skills in learning is by using Contextual Teaching and Learning. Contextual Teaching and Learning (CTL) is a learning model that provides facilities for student learning activities to find, manage, and discover concrete learning experiences that are linked to students' real lives. So this article was created with the aim of providing references related to learning models which in their application can improve student learning outcomes in schools. This study uses a meta-analysis with the calculation of effect size . Collecting data for this research by reviewing and exploring various journals related to Contextual Teaching and Learning. The meta analysis used is quantitative because it uses numerical calculations